Language learning beliefs and gender dynamics of university students in Egypt: an exploratory study - Mohamed, HebatAllah Abdel Aal (AUC Knowledge Fountain, 2015)
The present study contributes to the growing body of research in Second Language Acquisition (SLA) literature on foreign language learners' beliefs about language learning. It aims at exploring students’ beliefs about language learning in an English-medium university in Cairo, Egypt and examining the gender dynamics that shape and sustain those beliefs. The study adopted a mixed-methods data collection approach, data was collected using a questionnaire and interviews. Sixty-five first year students took a modified version of Horwitz’s (1987) Beliefs about Language Learning Inventory (BALLI). Nine participants were interviewed for an in-depth exploration of their language learning beliefs. The results showed that the lucrative future careers foreign language learning in Egypt promises is the primary reason students are interested in investing in learning English. The findings also revealed a linguistic tension between Arabic and English in Egypt with English being seen by some participants as more useful for their academic studies and their projected future careers. Others, however, expressed concern about maintaining the status of Arabic as a national language, given the ever-increasing demand for English in academic institutions and in the job market. In terms of gender dynamics, the findings revealed that gender differences as a variable is not to be assumed. In the specific population which participated in the study, there was little evidence in their intention to follow traditional societal norms proscribing women joining the workforce. Consequently, other linguistic and social variables ought to be taken into account for more significant research findings. The data, however, did reveal intriguing findings regarding gendered associations towards specific foreign languages like French and German which reflect a promising area for future research.